From Gerhard Kubik: West Berlin - Kubik, Gerhard (International Library of African Music, 1983)
Under the directorship of Dr Artur Simon, the Ethnomusicological Department of the Museum für Völkerkunde, West Berlin, organised in June 1983 a week of African music performances and demonstrations under the title “ Tage Afrikanischer Musik” (Days of African Music).
Keywords: African Music